Плечовий одяг скіф’янок - Клочко, Л.С. (Археологія, 1992)
У статті висвітлюються результати дослідження одного з елементів скіфського костюма — плечового одягу. Автор, аналізуючи зображення скіф’янок, археологічні матеріали, відзначає відправні точки для реконструкції силуету та крою різних форм вбрання. Костюм — одно из достижений культуры и поэтому изучение его раскрывает многие аспекты жизни общества.
Существенный элемент костюма — наплечная одежда. Форма одеяний, способы их создания, т. е. крой, отражают этнографические особенности племен, позволяют установить общие корни в происхождении различных этносов, их контакты и взаимодействие. Сейчас мы еще не располагаем материалами, чтобы ответить на многие вопросы, поэтому автор ограничивает задачи статьи описанием результатов изучения женской наплечной одежды. Исследование изобразительных памятников выявило основной тип кроя, который был характерен для Скифии. Это так называемый туникообразный крой. Выделяются два его варианта: а) стан одежды состоит из двух полотнищ, б) в основе стана одно центральное полотнище и боковины. Археологические фрагменты одежды — металлический декор, расположение которого подчинено определенным закономерностям. Анализ несъемных украшений — аппликаций — позволяет определить основные точки для реконструкции не только силуэта убранства, но и его крой.
В костюме скифянок бытовали такие формы наплечной одежды, как платье, куртка, халат, т. е. сочетаются накладные и распашные одежды. Этнокультурную характеристику составляют аппликации, оформление ворота, рукавов. A costume belongs to the culture achievements, so its examination reveals many aspects of life of any society.
The essential element of a costume is an «on-shoulder» garment. The design of cloths, the way of making them — a pattern cut — reflects ethnographic peculiarities of the tribes enabling to determine common roots in the origin of different ethnic groups, their contacts and interaction. Not all the evidence is available for us now to answer all the questions, that’s why the author confines himself to the exposition of the investigation results concerning women’s «on-shoulder» garments. Examination of some fine art memorials revealed the main cut pattern that was typecal of Scythia. It was the so-called tuniclike cut. Two patterns of this cut are distinguished: a) the garment base consists of two pieces; b) the garment base consists of one central piece and two lateral ones. Among the archaeologic fragments of the garment is a metallic decoration whose location is subject to certain regularities. The analysis of nonremovable ornaments — appliques — enables us to find out the main points for reconstructiong not only the garment’s silhouette but the cut as well. Such kinds of «on-shoulder» garments as dresses, coats (jackets), dressing- gowns, etc. were typical of Scythian women’s costumes, i. e. the combination of «robe- pattern» and «wrap over-pattern» garments. Appliques, design and decoration of collars and sleeves contribute distinctive features to ethnic culture.